ANALISIS PENDAPATAN DAN NILAI TAMBAH USAHA TAHU PADA INDUSTRI RUMAH TANGGA â€œWAJIANTOâ€ DI DESA OGURANDU KECAMATAN BOLANO LAMBUNU KABUPATEN PARIGI MOUTONG - Wiyono, Rukavina Baksh, Tuso (AGROTEKBIS, 2015)
This research is made in intention to know how many income and added value of the business of ?WAJIANTO? in Countryside of Ogurandu of Subdistrict of Bolano Lambunu of Regency of Parigi Moutong. This research were done during August 2014. Respondent selection is made with observation which is watching over the situation in the field directly and interviewing the owner or the tofu industry workers by using quisioner. Analysis data that used is analysis descriptive which is uses to know the general illustration of the business of tofu industry and the analysis quantity which is income analysis and added value of hayami. The result of research shows that the income of the home industry ?WAJIANTO? by producting tofu during August 2014 is Rp. 28.000.000, profit Rp. 10.414.789 and added value Rp. 10.337,72/kg for every 1 kg of soybeans will produce 0,7 kg tofu.